The Effect of Simulation Game Learning on Increasing Entrepreneurship Values and Children's Independence - Yulia Trisdiana; Hendratno Hendratno; Miftakhul Jannah (AL-ISHLAH: Jurnal Pendidikan, 2022)
Entrepreneurship programs can be used as a method of career guidance for early childhood. This study aims to determine the effect of Simulation Game Learning on Increasing Entrepreneurship Values and Children's Independence. Through this program, it has indirectly introduced the types of careers to children. This research is a type of quantitative research, with a quasi-experimental research method. The population in this study were the children of group B at Batik Kwadengan Barat Kindergarten and Dharma Wanita Persatuan Lemahputro TK as many as 40 students, class B TK Batik Kwadengan Barat amounted to 20 students as the experimental class and class B TK Dharma Wanita Persatuan Lemahputro amounted to 20 students as control class. Determination of the sample from the population using non-probability sampling. The collected data was then analyzed using statistical analysis to determine the effect of the independent variable on the dependent variable in the 2 groups with treatment only given to the experimental group. The statistical analysis in this study was carried out in 3 stages, namely: Instrument testing consisting of validity and reliability tests, Classical Assumption Test consisting of normality and homogeneity tests followed by hypothesis testing. Based on the test results, it is known that the instrument is valid and reliable and the data is normally distributed and homogeneous. The test results show that there is an effect of Learning Simulation Games on Increasing Entrepreneurship Values and Children's Independence. This is indicated by the significant difference in entrepreneurial development between the control group and the experimental group . As a reference, kindergarten teachers can apply simulation methods to develop children's entrepreneurial abilities and independence.